The desire [large type] - Walsh, Dan, 1957-; Smalley, Gary (Walsh, Dan, 1957- Restoration series, 2014)
For two years, Allen and Michele have been trying to have a baby. For Michele, it has become an obsession. But Allen seems content to spend his time -- and their money -- saving orphans in Africa. As Michele researches their options for fertility treatments, she begins to resent Allen's divided attention. And yet, God has a plan for Allen and Michele that they could never have imagined. All it takes to set it in motion is a change of heart ...